2007
DOI: 10.1073/pnas.0702000104
|View full text |Cite
|
Sign up to set email alerts
|

Csrp1 regulates dynamic cell movements of the mesendoderm and cardiac mesoderm through interactions with Dishevelled and Diversin

Abstract: Zebrafish Csrp1 is a member of the cysteine-and glycine-rich protein (CSRP) family and is expressed in the mesendoderm and its derivatives. Csrp1 interacts with Dishevelled 2 (Dvl2) and Diversin (Div), which control cell morphology and other dynamic cell behaviors via the noncanonical Wnt and JNK pathways. When csrp1 message is knocked down, abnormal convergent extension cell movement is induced, resulting in severe deformities in midline structures. In addition, cardiac bifida is induced as a consequence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…Of the most relevant findings, metabolic pathway analysis suggests that ketone-body formation is upregulated through an alternative pathway. Starvation and diabetes mellitus induce an upregulation of glucocorticoid signaling, resulting in elevated levels of Pdk4, 42 which we also observed in our study. Pdk4 is the key mediator in preventing the conversion of pyruvate to acetyl-CoA by inhibiting pyruvate dehydrogenase complex C. In the liver, this inhibition enables ketone-body synthesis from fatty acids and ketogenic amino acids rather than 3 carbon compounds, which are then available for gluconeogenesis in the liver to maintain blood glucose levels.…”
Section: Discussionsupporting
confidence: 75%
“…Of the most relevant findings, metabolic pathway analysis suggests that ketone-body formation is upregulated through an alternative pathway. Starvation and diabetes mellitus induce an upregulation of glucocorticoid signaling, resulting in elevated levels of Pdk4, 42 which we also observed in our study. Pdk4 is the key mediator in preventing the conversion of pyruvate to acetyl-CoA by inhibiting pyruvate dehydrogenase complex C. In the liver, this inhibition enables ketone-body synthesis from fatty acids and ketogenic amino acids rather than 3 carbon compounds, which are then available for gluconeogenesis in the liver to maintain blood glucose levels.…”
Section: Discussionsupporting
confidence: 75%
“…Although a primary role of non-canonical Wnt signaling was to govern convergence and extension movements, studies had also shown that the three Wnt noncanonical ligands, wnt4a, wnt11, and wnt11r, redundantly regulated midline convergence of organ primordia, in zebrafish embryos (31,41). In this study, we showed that the midline migration of heart precursors and pancreas precursors required expression of eaf1 and eaf2/u19 (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…CRP1 has been reported in many different cellular functions: acting as a transcriptional cofactor (Chang et al, 2003), suppressing cell proliferation, protecting cells from stress-induced death (Latonen et al, 2008), regulating cell movement during zebrafish development (Miyasaka et al, 2007), and promoting neointima formation (Lilly et al, 2010). It has also been demonstrated that CRP1 regulates actin filament bundling via direct interaction with actin (Tran et al, 2005;Jang and Greenwood, 2009).…”
Section: Introductionmentioning
confidence: 99%